The dynamic oral–gastric microbial axis connects oral and gastric health: current evidence and disputes - Mengying Xia; Lei Lei; Linyong Zhao; Wenqing Xu; Hongyu Zhang; Mingming Li; Jiankun Hu; Ran Cheng; Tao Hu (npj Biofilms and Microbiomes)
Abstract Emerging evidence indicates that oral microbes are closely related to gastric microbes and gastric lesions, including gastric atrophy, intestinal metaplasia and gastric cancer (GC). Helicobacter pylori is a key pathogen involved in GC. However, the increasing prevalence of H. pylori-negative GC and gastric dysbiosis in GC patients emphasize the potential role of other microbial factors. In this review, we discussed the current evidence about the relationship between the oral–gastric microbial axis and oral and gastric health. Epidemiologic evidence indicates that poor oral hygiene is related to greater GC risk. Multiple oral-associated microbes are enriched in the stomach of GC patients. Once colonizing the stomach, oral-associated microbes Streptococcus anginosus and Prevotella melaninogenica, are involved in gastric inflammation or carcinogenesis. Microbial metabolites such as lactate, nitrite, and acetaldehyde promote malignant transformation. The stomach, as a checkpoint of microbial transmission in the digestive tract, is of great importance since the link between oral microbes and intestinal diseases has been emphasized. Still, new technologies and standardized metrics are necessary to identify potential pathogenetic microbes for GC and the core microbiota, interactions, richness, colonization, location and effect (CIRCLE). In the future, oral microbes could be candidates for noninvasive indicators to predict gastric diseases.